NON-SPECIFIC CONGENITAL CONNECTIVE TISSUE DISORDERS AS AN INDEPENDENT PREDICTOR OF STRUCTURAL AND FUNCTIONAL ARTERIAL CHANGES - A. A. Semenkin; O. V. Drokina; G. I. Nechaeva; L. A. Zhivilova; A. B. Zhenatov (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To assess the impact of non-specific congenital connective tissue disorders (CCTD) on the changes in arterial stiffness and endothelial function; to study the role of CCTD as an independent predictor of structural and functional arterial changes.Material and methods. The study included 147 18–50-year-old men and women with CCTD and 85 healthy volunteers, comparable by age and gender (controls). All participants underwent a screening assessment of cardiovascular risk factors (RFs) and the assessment of heart rate variability (HRV), pulse wave velocity (PWV) at baseline (PWVbas) and after sublingual administration of nitroglycerin (PWVntg), and endothelium-dependent vasodilatation (EDVD), assessed by photopletismography.Results. Compared to the control group, CCTD patients had lower values of body mass index (p<0,001), waist circumference, WC (p<0,001), hip circumference, HC (p<0,001), WC/HC ratio (p<0,005), systolic blood pressure (p<0,05), total cholesterol (p<0,001), low-density lipoprotein cholesterol (p<0,005), atherogenicity index (p<0,05), and triglycerides (p<0,005). Moreover, CCTD patients were characterized by sympathetic activation, increased PWVbas (p<0,001), PWVntg (p<0,05), and EDVD (p<0,001). According to the results of stepwise multivariate analyses of the whole sample data, CCTD was a significant independent predictor of PWVbas (p<0,001), PWVntg (p<0,005), and EDVD (p<0,005 and <0,05 in men and women, respectively).Conclusion. Patients with CCTD demonstrated increased arterial stiffness and endothelium-dependent vasodilatation, compared to healthy controls. Independently from cardiovascular RFs and autonomic dysregulation, CCTD is a significant predictor of structural and functional arterial changes and can also have a prognostic value. These findings should be taken into account in the studies which assess vascular parameters.